Interpretation of special considerations for 2021 CDC guidelines on the diagnosis and the treatment of syphilis - Xinying LENG; Huachun ZOU; Leiwen FU; Wujian KE (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Syphilis, a sexually transmitted disease, is caused by Treponema pallidum subspecies pallidum. Although syphilis is curable with appropriate antibiotics, there are still challenges in the management of syphilis due to its diversity of clinical manifestations, difficulty in the interpretation of test results and the diagnosis of neurosyphilis. Therefore, U.S. CDC released the latest guidelines on the diagnosis and the treatment of syphilis in 2021. Aiming to assist healthcare providers in the management of syphilis, we interpret this guideline mainly on the special considerations of different tests, reverse sequence algorithm, tests of neurosyphilis, syphilis during pregnancy, Jarisch-Herxheimer reaction and the management of sex partners.